WAQF LĀZIM DALAM MUSHAF AL-QUR’AN STANDAR INDONESIA DAN MUSHAF MADINAH: ANALISIS JUMLAH, POLA PENEMPATAN, DAN PENGARUHNYA TERHADAP PENAFSIRAN AYAT - Najib Irsyadi (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
The study of al-wqaf wa al-ibtidā' is one of the branches of 'ulum al-Qur'ān which is very important to be studied by Muslims. Moreover, today the Qur'anic mushafs circulating in the world have differences, both in terms of the signs used, as well as waqf and number. This issue has attracted the attention of many scholars. However, the comprehensive research on how the image of waqf lāzim among the different mushafs of the Qur’an, especially  the mushafs wich are widely circulated in Indonesian society, and its effect on interpretation is still rare. This paper is present in order to find scientific answers to the main question, what is the different in amount of waqf lāzim, its placement pattern, and its effect on interpretation between the Indonesian Standard Qur'an Mushaf and Madinah Mushaf. This study uses a comparative-analytical method, which is to compare the differences between two or more groups of a certain variable, in this case comparing the differences in the placement of waqf lāzim between the Indonesian Standard Qur'an Mushaf and Madinah Mushaf. After being compared as a whole, it is then analyzed about the causes-effects and factors that influence of these differences on interpretation. There are several points that can be concluded, there are 86 waqf lāzim places in the Indonesian Standard al-Qur'an Mushaf; 53 places in the middle of the verse and 33 places at the end. Meanwhile, in Madinah Mushaf, there are 22 verses marked with waqf lāzim, all of which are in the middle of the verse. This difference stems from the different patterns of placement of waqf lāzim, which are analyzed based on grammatical understanding and meaning. The selection of a waqf lāzim cannot be separated from the tendency of the interpretation of the verse desired by the Mushaf. After investigating, two main factors, internal and external, play a big role in influencing the differences in determining waqf lāzim between these two mushaf.